PENGARUH MODEL LATIHAN DAN KOORDINASI TERHADAP KETERAMPILAN EKSTRAKURIKULER BOLA BASKET SD NEGERI POKOH 2 NGEMPLAK - Ardiyanto, Asep (MALIH PEDDAS, 2015)
This study aims to investigate: (1) the different effects of the guided discovery style model training and command style model training on basketball skills of students, (2) the different effects on basketball skills of students who have high and low coordination, and (3) the interaction effects between training models of guided discovery style and command style with coordination (high and low) on the basketball skills of students.This research was an experiment. The population comprised 43 basketball extracurricular students. A sample of 24 students was established using the purposive sampling technique. The instruments of this research were wall bounce pass test to measure eye-hand coordination and Sekolah Tinggi Olahraga (STO) test to measure the basketball skills. The data were analyzed using the two-way ANAVA analysis.The results of the study are as follows. (1) There is no different effect between guided discovery style model training and command style model training on the basketball skills of the students. (3) There is an effect difference on the basketball skills of the students who have high and low coordination. (4) There is no a significant interaction between model training and coordination on the basketball skills of students.